Assessment Framework to Monitor and Evaluate e-Government Procurement Systems in India - World Bank (Washington, DC, 2014)
This working paper elaborates on an assessment framework to monitor and evaluate e-government procurement systems in India. This is relevant due to the fact that many government agencies have sought to extend use of e-tendering system implemented in their organization to handle procurement in World Bank funded projects. The World Bank has developed a procedure to assess e-tendering systems for compliance to certain guidelines laid down by Multilateral Development Banks. The World Bank prefers to work with the Government of India in development of a robust mechanism for assessment of e-tendering systems instead of independently assessing e-tendering systems as has been done till date. The Government of India has already established a set-up under Standardization, Quality and Testing Certification (STQC) for assessment of e-procurement systems. From its assessment experience, the World Bank has found that the e-procurement applications deployed in many of the e-procurement installations assessed by the Bank were STQC certified, yet there were several issues with the e-procurement systems. A new concept model for assessment of e-procurement systems is proposed herein as an evolved version of the existing STQC s guideline to address the critical issues identified and the improvements suggested to the STQC s guideline. The assessment framework explained in this report could also be used as a vehicle to implement policy in other federated e-governance systems such as e-District and State Data Center (SDC). Therefore, the assessment framework concept explained herein has wider application in implementation of e-governance policy.